POSTMODERNISME SEBAGAI PANDANGAN DUNIA DALAM NOVEL LITTLE WHITE HORSE KARYA ELIZABETH GOUDGE - Muarifuddin Muarifuddin; Rahmawati Azi (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2017)
This paper is an output of Penelitian Dosen Muda PDP entitled Pandangan Dunia Elizabeth Goudge dalam Novel Little White Horse. This research used genetic structuralism point of view where the postmodernism is involved to be the worldview of this novel, since genetic structuralism requires a philosophical point of view to be the companion of its concept. In this case, postmodernism appears to be the worldview of this novel. Since fantasy literature always be treated as merely the popular culture product, then the study about them never involve the spirituality and the philosophical thinking. By applying genetic structuralism point of view in this research, the writer could broaden the scope of study about fantasy work. Some aspects namely the struggle of individual subject against the mainstream can be revealed by utilizing the destructuring concept in genetic structuralism. The kind of data is a qualitative descriptive. The data is collected by reading the novel comprehensively to find the data where the theory is required. The analysis is done by using the whole and the part method from genetic structuralism. The result of this research showed that Little White Horse novel is postmodernism in term of form and ideology. The form of Little White Horse is a collaboration between the contentism and the Coterie fiction and it took Whiteheadian postmodernism as its worldview. Whiteheadian postmodernism concept consists of the immanence of God and the interspecies relationship. This ideology is a result of the destructuring and restructuring of the trans-individual subject integrated in Romantic Novel Association (RNA) where Goudge is involved in opposing the secular and the destructive of modern point of view. Key words: wordview, genetic structuralism, transindividual subject, postmodernism